2018
DOI: 10.7717/peerj.5166
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing confounders and increasing data quality in murine models for studies of the gut microbiome

Abstract: Murine models are widely used to explore host-microbe interactions because of the challenges and limitations inherent to human studies. However, microbiome studies in murine models are not without their nuances. Inter-individual variations in gut microbiota are frequent even in animals housed within the same room. We therefore sought to find an efficient and effective standard operating procedure (SOP) to minimize these effects to improve consistency and reproducibility in murine microbiota studies. Mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 45 publications
5
42
0
Order By: Relevance
“…29 Furthermore, the variables cage, breeding and experiment number were variables that were associated with significant differences in the gut microbiota composition, which is in line with other murine studies. 29 Furthermore, the variables cage, breeding and experiment number were variables that were associated with significant differences in the gut microbiota composition, which is in line with other murine studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…29 Furthermore, the variables cage, breeding and experiment number were variables that were associated with significant differences in the gut microbiota composition, which is in line with other murine studies. 29 Furthermore, the variables cage, breeding and experiment number were variables that were associated with significant differences in the gut microbiota composition, which is in line with other murine studies.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, we found significant inter-individual variation in the murine gut microbiome, a finding that has been reported previously. 29 Furthermore, the variables cage, breeding and experiment number were variables that were associated with significant differences in the gut microbiota composition, which is in line with other murine studies. [30][31][32] According to the number of significantly different abundant genera, the variation of the gut microbiota between the cages and individual experiments had the highest impact on the gut microbiota in our study.…”
Section: Discussionsupporting
confidence: 86%
“…breast-milk feeding and ingest the soft faeces of dams) and indigenous environment microbiome (Hufeldt, et al, 2010;Rogers, et al, 2014;Ericsson, et al, 2015;Yang, et al, 2017;Korpela, et al, 2018;Martinez, et al, 2018). Previous studies investigated the role of sex in adult animals' gut microbiota suggested that the significant difference of gut microbial composition between sexes was caused by sex hormones (Org, et al, 2016;Miyoshi, et al, 2018). However, Steegenga, et al (2014) indicated that these sexual microbial differences do not present in the young animals and are only detected after puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while Bacteroidetes and Firmicutes dominate in the microbiota of many laboratory rodents (e.g., mice, rats, hamsters) [3537], marked differences between the rodent and human GIT microbiota at the genus level indicate that rodent studies may not be generalizable to humans [38]. Furthermore, individual rodents may vary greatly in their microbiota even when co-housed; thus, rigorous experimental techniques are required to ensure consistency in experiments [39]. …”
Section: The Healthy Microbiota and Its Role In Immune Homeostasismentioning
confidence: 99%
“…Many studies have shown that the GIT microbiota composition differs in adult male and female rodents [39, 4346]. For example, while the pro-inflammatory Lactobacillaceae are more abundant in females, the highly pro-inflammatory Ruminococcaceae and Rikenellaceae are more prevalent in males [43].…”
Section: Sex Differences In the Git Microbiota And Immunity—rodent Stmentioning
confidence: 99%